Conflicto de pareja y su incidencia en la estabilidad mental de una mujer de 26 años, del cantón Babahoyo, Provincia de Los Ríos - Coronel Barzola, Cindy Paola (2022)
Couple conflicts have taken power in recent years, people tend to normalize this type of behavior, but when symptoms appear at a cognitive, affective, social and somatic level, it is very likely that it is directed to a mental disorder. Reason for which, the present case study focuses on what thinking in an unrealistic way can be generated due to couple conflicts. The objective of the case study is to demonstrate how couple conflict affects the mental stability of a 26-year-old woman from the Babahoyo canton, Los Ríos province. For the investigation, an exhaustive search of verified information was carried out, with its respective bibliography, in addition to putting it into practice together with the patient, through psychotherapeutic sessions. Techniques and instruments were applied, which are detailed below: the semi-structured interview with its clinical history instrument and the psychometric test technique with its instruments: the Hamilton anxiety scale, the Rosenberg self-esteem scale and the characterological test. by Mauricio Gex. Which, together with the reason for consultation, showed a generalized anxiety disorder. Attached is a model of a psychotherapeutic scheme, specially prepared for the patient, through Aaron Beck's cognitive behavioral therapy.